How free will US trade remain? - Robert G. Wertheimer (Intereconomics, 1972)
The final stage of the Kennedy Round tariff cuts in operation since the beginning of this year apparently has brought a minimum of obstacles to imports into the US. Nevertheless, even though rising US imports seem to prove the point of a far reaching trade liberallsation, leadership of the United States in this field has come to a grinding halt.
Keywords: 330; Foreign Trade